2007
DOI: 10.1073/pnas.0606974104
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the MAP kinase DYF-5 affects docking and undocking of kinesin-2 motors and reduces their speed in the cilia of Caenorhabditis elegans

Abstract: In the cilia of the nematode Caenorhabditis elegans, anterograde intraflagellar transport (IFT) is mediated by two kinesin-2 complexes, kinesin II and OSM-3 kinesin. These complexes function together in the cilia middle segments, whereas OSM-3 alone mediates transport in the distal segments. Not much is known about the mechanisms that compartmentalize the kinesin-2 complexes or how transport by both kinesins is coordinated. Here, we identify DYF-5, a conserved MAP kinase that plays a role in these processes. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
181
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(205 citation statements)
references
References 46 publications
22
181
2
Order By: Relevance
“…Mutations in rhodopsin or protein transport machinery of the cilia (e.g., Kif3a or IFT mutants) cause accumulation of rhodopsin in the photoreceptor cell body and result in photoreceptor cell death. Absence of Dyf-5, a nematode homolog of Mak, affects the motility of kinesin motors and IFT particles in the cilia (14). Similarly, we identified aberrant accumulations of IFT and kinesin in the Mak-KO photoreceptor cilia.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Mutations in rhodopsin or protein transport machinery of the cilia (e.g., Kif3a or IFT mutants) cause accumulation of rhodopsin in the photoreceptor cell body and result in photoreceptor cell death. Absence of Dyf-5, a nematode homolog of Mak, affects the motility of kinesin motors and IFT particles in the cilia (14). Similarly, we identified aberrant accumulations of IFT and kinesin in the Mak-KO photoreceptor cilia.…”
Section: Discussionmentioning
confidence: 59%
“…In the distal segment of the amphid channel cilia in dyf-5 animals, singlet microtubules were observed (14). We observed singlet microtubules in outer-segment axonemes, which are positioned near the disk clefts, in both wild-type and Mak-null retinas (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, depletion of Ccrk in cultured cells results in elongated cilia (25). In addition, a forward genetic screen of C. elegans identified dyf-5 kinase, an ortholog of LF4, as a regulator of ciliary length and function (7). In humans, loss of MAK, a homolog of LF4 and paralog of ICK, results in elongated cilia in photoreceptor cells, causing retinitis pigmentosa (5,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that Long Flagellar 4 (LF4), the homolog of RCK kinases in Chlamydomonas, is localized in flagella, and null mutants of LF4 possess flagella that are twice as long as those in wild types (6). Furthermore, in Caenorhabditis elegans, disruption of the RCK homolog dye-filling defective 5 (dyf-5) results in the elongation of neuronal cilia, whereas overexpression of DYF-5 leads to the shortening of cilia (7). Although the physiological functions and downstream targets of RCK family kinases are not well understood in higher organisms, these studies suggest that the role of RCK family kinases in controlling ciliary length may be well conserved from single-celled organisms to mammals.…”
mentioning
confidence: 99%